The Impact of Application of Fingerprint Absention on Work Discipline in PT Mustika Ratu Tbk Jakarta - Wasilatun Nikmah; Otto Siregar; Henny Armaniah (Journal of Research in Business, Economics, and Education, 2020)
Discipline is very important to achieve company goals. This study aims to determine the effect of fingerprint attendance on employee performance at PT. Mustika Ratu, T.bk Jakarta. The method used is a quantitative analysis method. Data obtained by distributing questionnaires to employees by taking as many as 40 employees. The technique used is the correlation test, the coefficient of determination test, and the regression equation test. Based on the calculation of SPSS, the correlation coefficient results of 0.824 shows that the relationship is very strong between fingerprint attendance and work discipline. Fingerprint attendance affects 68.0% of work discipline, while the remaining 32.0% is affected by other factors not examined in this study. Based on the results of the SPSS obtained the following regression equation Y = 6.910 + 0.821 shows that without absenteeism the performance value of 6.910.